Assessing agritourism-integrated rural human settlement environment under the “dual-carbon” goal: evidence from Zhejiang, China - Shuaijun Lin; Hongfeng Zhang; Johnny F. I. Lam (Journal of Asian Architecture and Building Engineering)
With the full implementation of the rural revitalization strategy, the upgrading of tourism consumption, and the impact of global climate change, the Chinese Government is seeking a green transformation and upgrading of agriculture, and an agritourism-integrated human settlement environment is one of the most important means of coordinating the relationship between people and land and promoting the green development of the village. However, there is a lack of scientific evaluation research on rural human settlement environments integrated with agritourism. The purpose of this Research is to explore the establishment of an evaluation system of rural human settlement environment indicators based on the “Dual-carbon” perspective of agrotourism integration, to assign weights to the indicators at each level by using the AHP analysis method, to validate the agrotourism-integrated villages by using the BP neural network, to arrive at a generalizable AHP-BP evaluation model, and to use the AHP-BP evaluation model for the 22 agrotourism-integrated villages in Zhejiang Province of China to evaluate the human settlement environment in the rural areas of Zhejiang Province. Panel data from 22 samples of agritourism-integrated villages in Zhejiang Province of China were used as samples for empirical tests to verify the validity and feasibility of the model. The results show that this Research utilizes the AHP method to determine the weights of indicators at each level, finding that economic development and the natural environment are essential evaluation aspects. Meanwhile, the BP neural network model was applied to predict the scores of 22 sample villages, and the prediction results were highly correlated with the actual ones. The average absolute error of the model is only 1.18%, which verifies the accuracy of the model and can provide a reference for the governmental departments to monitor and evaluate the Agriculture and Tourism Integrated Rural Human Settlement Environment.